National Nosocomial Infection Surveillance System-based study in north eastern of Iran - Maliheh Ziaee; Reza Vafaeenejad; Gholamreza Bakhtiari; Irandokht Mostafavi; Maliheh Gheibi; Javad Mahmoudi Fathabadi; Mojtaba Taghvaei Ahmadi (Shahid Beheshti University of Medical Sciences, 2017)
among about 10% of hospitalized patients. HAIs increase mortality and morbidity and prolonged hospital stay not to mention considerable costs they impose on the health care system. The present study was conducted in order to evaluate the prevalence of HAIs based on National Nosocomial Infection Surveillance System in hospitals of Mashhad, Iran.   Methods: The current prevalence study of HAI was carried out in 26 hospitals using a protocol updated yearly in Mashhad, Iran. The Centers for Disease Control and Prevention-National Nosocomial Infections Surveillance were used to define four HAIs. All patients admitted to the hospitals during a one-year period (March 1, 2015-February 30, 2016) were recruited in the study. Data was extracted using Iranian nosocomial infection surveillance software.   Results: The overall prevalence rate of HAI in our study was 0.8% among the hospitals with the most frequent HAIs found to be pneumonia (25%), followed by urinary tract infections (20%), and blood stream infections (19%). The highest prevalence rate was observed in 15- to 65-year old patients with more than 50% related to surgical site infection. Also, the most frequently isolated micro-organism was acinetobacter. In addition, the highest seasonal prevalence was seen in winter with pneumonia as the most frequent infection. A total of 4988 pathogens were isolated with 30.33% of clinical confirmation and 69.66% of positive culture.   Conclusion: These findings emphasize the need for appropriate measures for prevention, screening, labeling, and isolation precautions for infected patients.